STRATEGI KOMUNIKASI BADAN PELAYANAN TERPADU DAN PENANAMAN MODAL DALAM MENERAPKAN KEBIJAKAN SISTEM ONE STOP SERVICE PADA MASYARAKAT KOTA PEKANBARU - Mahessa, Tessa Julien Julien; Wirman, Welly (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The Government who has the responsibility as service administrator needs to improve thequality of service with the priority of community needs. One Stop Service is an event organizer oflicensed and non-licensed, which has the process from proposal to documents publishing. Theaim of this research is to know the strategy of communication which has been done by anIntegrated Service Agency and Investment in implementing One Stop Service system policy to thecommunity in Pekanbaru.The writer used Qualitative-Descriptive method for this research, the informants are 6persons who have been selected with purposive sampling technique. The subjects of this researchwere the head of subsection of programming, the civil servants of Integrated Service Agency andInvestment Pekanbaru, and the community that using One Stop Service system. The types andsources of data used are primary and secondary data. The data collection technique of thisresearch was deep interview and documentations.Research result of communication strategy which has done by the Integrated ServiceAgency and Investment was to determine the target audience; community leaders, religiousleaders, and employers or society who will open a small business. Factors that have to beconsidered in the planning of public communication are; audience’s plannning, backgroundknowledge, and feeling. Plannings for communication message are; main message and messageorganizations. Media used for this research are printed media and electronic media.Keyword: Communication Strategy, One Stop Service.